Spatial Organization of Street Vendors around ICE BSD: An Analysis of Policy Compliance - Phen, Wiwien; Tjahjadi, Darren Jonathan; Komsiatun, Siti; Wijaya, Christian Wisaputra (Rumoh Journal of Architecture, 2025)
Street vendors (PKL) are informal sector entrepreneurs who typically have limited capital in trade or service-based businesses, aiming to meet the daily needs of the community. They tend to choose strategic and high-traffic locations to conduct their business activities. The management of street vendors has become a significant issue in public space governance, as it must support informal economic activities while maintaining environmental comfort. However, in many cases, the spatial arrangement of street vendors remains unstructured and tends to disregard government regulations. This study focuses on the area surrounding the Indonesia Convention Exhibition (ICE) in Bumi Serpong Damai (BSD), Tangerang. It aims to analyze the level of compliance of street vendors with government regulations concerning public space management and spatial layout in the ICE BSD area. The research methods include direct field observation and policy analysis. The findings indicate that most vendors do not fully comply with the spatial regulations, resulting in space-use conflicts, a decline in environmental aesthetics, and disruptions to visitor mobility. Factors influencing their level of compliance include a lack of rule dissemination, economic necessity, and inadequate supporting facilities. The recommendations of this study include enhancing dialogue between local authorities and vendors regarding applicable regulations (through more intensive socialization efforts), providing designated spaces or representative supporting facilities, and enforcing the rules more firmly while still accommodating the economic needs of the vendors. Well-managed vendor arrangements will foster harmony between economic function, environmental aesthetics, and the sustainability of public spaces around the ICE BSD area.